2011
DOI: 10.1016/j.patcog.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for surround suppression by steerable filters and multilevel inhibition with application to contour detection

Abstract: Psychophysical and neurophysiological evidence about the human visual system shows the existence of a mechanism, called surround suppression, which inhibits the response of an edge in the presence of other similar edges in the surroundings. A simple computational model of this phenomenon has been previously proposed by us, by introducing an inhibition term that is supposed to be high on texture and low on isolated edges. While such an approach leads to better discrimination between object contours and texture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…For this reason, numerous neural network approaches have been proposed that are inspired by the physiology of the primary visual cortex (Ben-Shahar and Zucker, 2004;Grigorescu et al, 2003Grigorescu et al, , 2004Hansen and Neumann, 2008;Huang et al, 2009;Li, 1998;Mundhenk and Itti, 2005;Papari et al, 2007;Papari and Petkov, 2011;Petkov and Westenberg, 2003;Tang et al, 2007a,b;Ursino and La Cara, 2004;Vonikakis et al, 2006;Zeng et al, 2011a,b). A neuron in such a model has a classical receptive field (cRF), often defined using a Gabor function, that receives input from the image.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, numerous neural network approaches have been proposed that are inspired by the physiology of the primary visual cortex (Ben-Shahar and Zucker, 2004;Grigorescu et al, 2003Grigorescu et al, , 2004Hansen and Neumann, 2008;Huang et al, 2009;Li, 1998;Mundhenk and Itti, 2005;Papari et al, 2007;Papari and Petkov, 2011;Petkov and Westenberg, 2003;Tang et al, 2007a,b;Ursino and La Cara, 2004;Vonikakis et al, 2006;Zeng et al, 2011a,b). A neuron in such a model has a classical receptive field (cRF), often defined using a Gabor function, that receives input from the image.…”
Section: Introductionmentioning
confidence: 99%
“…This technique extracts linear features, while suppressing texture elements of cluttered background. We also experimented with other approaches [20,10,28], but these are either not sensitive enough to extract faint edges of enclosures, or generate lots of clutter edges depending on the parameters used. The parameterless line segment detector [11], which is known to provide robust results for a large range of images, misses faint edges of enclosures.…”
Section: Data Used and Preprocessingmentioning
confidence: 99%
“…In order to remove small edges in highly textured regions, we use the inhibition term that suppress the response on the texture regions based on steerable filters [14]. It is computed by the convolution of the Gaussian gradient magnitude with the inhibition term (IT):…”
Section: Multi-scale Point Featuresmentioning
confidence: 99%
“…It can be shown that the difference of magnitude of Gaussian gradient and the inhibition term is the difference of Gaussian (DoG) feature [14] which provides useful edge information.…”
Section: Multi-scale Point Featuresmentioning
confidence: 99%
See 1 more Smart Citation